HUBUNGAN FUNGSI SEKSUAL DENGAN KEPUASAN SEKSUAL WANITA PENGGUNA KONTRASEPSI HORMONAL JANGKA PANJANG - Sabatina Windyaningrum; Wenny Rahmawati; Dwi Murwani K.W.M. Justus (JOMIS (Journal of Midwifery Science), 2026)
Sexual dysfunction is a common side effect reported by hormonal contraceptive users. Sexual dissatisfaction resulting from dysfunction in either partner can diminish quality of life and marital harmony. This study aims to analyze the correlation between sexual function and sexual satisfaction among women using long-term hormonal contraception (more than 3 years). This cross-sectional study was conducted from August to November 2024 at TPMB Mudjiasri, Wagir District, Malang Regency. A total of 30 respondents were selected using a total sampling technique based on specific inclusion criteria. Sexual function was evaluated using the Female Sexual Function Index (FSFI) questionnaire, while sexual satisfaction was assessed via the Sexual Satisfaction Scale for Women (SSS-W). Data were statistically analyzed using the Chi-square test.The results showed that among the 28 respondents experiencing sexual dysfunction, 25 (83.3%) reported sexual dissatisfaction. Conversely, all respondents with normal sexual function (6.7%) reported being satisfied. Statistical analysis yielded a p-value of 0.001 (p < 0.05), proving a significant correlation between sexual function and sexual satisfaction. Decreased estrogen levels due to long-term hormonal use are known to inhibit lubrication and libido, thereby reducing coital frequency.This study recommends that healthcare providers enhance education and intensive counseling regarding the sexual impacts of hormonal contraceptives. Additionally, long-term users are advised to seek regular consultations or consider non-hormonal contraceptive alternatives to maintain reproductive health and marital harmony.